2014
DOI: 10.4322/floram.2014.013
|View full text |Cite
|
Sign up to set email alerts
|

Teste de Condutividade Elétrica em Sementes de Bowdichia virgilioides Kunth

Abstract: RESUMOO objetivo deste trabalho foi adequar a metodologia do teste de condutividade elétrica (CE), além de determinar a qualidade fisiológica de sementes de B. virgilioides. As sementes foram separadas em três sublotes, de acordo com a coloração do tegumento (1-amarela, 2-alaranjada e 3-vermelha/preta). No teste de CE, estudaram-se três quantidades de sementes (25, 50 100), três volumes de água (25, 50 e 100 mL) e seis tempos de embebição das sementes (12, 24, 36, 48, 60 e 72h), a 25 °C, com seis repetições. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
3
8
0
9
Order By: Relevance
“…These results corroborate with Dalanhol et al (2014), which evaluated physiological quality of three Bowdichia virgilioides Kunth seed lots of different colours, and observed that the yellow seeds lot presented greater percentage of germination (98%), while the lot with orange and red seeds presented 85.3% and 31.3% of germination, respectively. The germination test is performed in optimal conditions, that's why it is not sensitive to detect small variation of vigour in the seed lots (Marcos Filho, 1999); nevertheless, in this study, the test ranked the lots in different germination levels.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results corroborate with Dalanhol et al (2014), which evaluated physiological quality of three Bowdichia virgilioides Kunth seed lots of different colours, and observed that the yellow seeds lot presented greater percentage of germination (98%), while the lot with orange and red seeds presented 85.3% and 31.3% of germination, respectively. The germination test is performed in optimal conditions, that's why it is not sensitive to detect small variation of vigour in the seed lots (Marcos Filho, 1999); nevertheless, in this study, the test ranked the lots in different germination levels.…”
Section: Resultssupporting
confidence: 89%
“…White clover seeds have uneven ripeness, resulting in plants with tegument colour variation, ranging from yellow to brown-red (Costa et al, 2014). According to Dalanhol et al (2014), the same occurs with Bowdichia virgilioides Kunth seeds, and the tegument colour variation is closely related to physiological quality of seed lots. Atis et al (2011) observed that tegument colour of red clover (Trifolium pratense) seeds may indicate their quality, and greater germination and vigour values were found for yellow seeds.…”
Section: Resultsmentioning
confidence: 95%
“…The beginning of seed deterioration process is characterized by the de-structuring of the cell membrane system. The electrical conductivity test provides information together with other vigor analysis during the storage period (Milani et al 2012, Dalanhol et al 2014. The values for electrical conductivity of L. albescens seeds, after 24 and 48 hours, showed no significant differences between storage locations (laboratory and cold room temperature).…”
Section: Seed Conservation Testmentioning
confidence: 99%
“…The electric conductivity test was directly related to the cell membranes integrity, since the levels reorganization of the membrane and the reparation of damages are higher on seeds with greater vigor (DALANHOL et al, 2014), as those kept at 34% of relative humidity. This test has been efficient to evaluate the membrane permeability during seed deterioration on arborous species (ORTIZ et al, 2015).…”
Section: Discussionmentioning
confidence: 99%